Intraoperative EMG recovery patterns and outcomes after RLN traction-related amplitude decrease during monitored thyroidectomy - Chiu, Kuan-Lin; Lien, Ching-Feng; Wang, Chih-Chun; Wang, Chien-Chung; Hwang, Tzer-Zen; Shih, Yu-Chen; Yu, Wing-Hei Viola; Wu, Che-Wei; Dionigi, Gianlorenzo; Huang, Tzu-Yen; Chiang, Feng-Yu (Frontiers in Endocrinology, 2022)
Objectives: Traction injury is the most common type of recurrent laryngeal nerve (RLN) injury in thyroid surgery. Intraoperative neuromonitoring (IONM) facilitates early detection of adverse electromyography (EMG) effect, and this corrective maneuver can reduce severe and repeated nerve injury. This study aimed to evaluate intraoperative patterns and outcomes of EMG decrease and recovery by traction injury. Methods: 644 patients received nerve monitored thyroidectomy with 1142 RLNs at risk were enrolled. Intermittent IONM with stimulating dissecting instrument (real-time during surgical procedure) and trans-thyroid cartilage EMG recording method (without electrode malpositioning issue) were used for nerve stimulation and signal recording. When an EMG amplitude showed a decrease of >50% during RLN dissection, the surgical maneuver was paused immediately. Nerve dissection was restarted when the EMG amplitude was stable. Results: 44/1142 (3.9%) RLNs exhibited a >50% EMG amplitude decrease during RLN dissection and all (100%) showed gradual progressive amplitude recovery within a few minutes after releasing thyroid traction (10 recovered from LOS; 34 recovered from a 51-90% amplitude decrease). Three EMG recovery patterns were noted, A-complete EMG recovery (n=14, 32%); B-incomplete EMG recovery with an injury point (n=16, 36%); C-incomplete EMG recovery without an injury point (n=14, 32%). Patients with postoperative weak or fixed vocal cord mobility in A, B, and C were 0(0%), 7(44%), and 2(14%), respectively. Complete EMG recovery was found in 14 nerves, and incomplete recovery was found in another 30 nerves. Temporary vocal cord palsy was found in 6 nerves due to unavoidable repeated traction. Conclusion: Early detection of traction-related RLN amplitude decrease allows monitoring of intraoperative EMG signal recovery during thyroid surgery. Different recovery patterns show different vocal cord function outcomes. To elucidate the recovery patterns can assist surgeons in the intraoperative decision making and postoperative management.